Dementia of the Alzheimer type: current state of the problem - N.A. Tyuvina; V.V. Balabanova (Неврология, нейропсихиатрия, психосоматика, 2014)
The current knowledge on epidemiology, diagnosis, and treatment of Alzheimer's disease and dementia of the Alzheimer type are presented. Various approaches to therapy based on current understanding of the pathogenesis of the degenerative process are discussed with allowance for the clinical features of the disease (psychopathologic symptoms and stage of the disease). Special attention is paid to compensatory therapy aimed at compensating for the deficit in cholinergic and glutamatergic neurotransmission.